ASPECTOS DE LA BIOLOGÍA, TAXONOMÍA Y CONTROL DE LAS ESPECIES DEL GÉNERO COLEOPHORA (LEPIDOPTERA: COLEOPHORIDAE) DE DISTRIBUCIÓN CHILENA (Acta Entomológica Chilena, 2022)
Coleophora versurella and C. mayrella are cosmopolitan species that were introduced in Chile. In Chilethe larvae of C. versurella feed on Amaranthus hybridus and occasionally on Chenopodium álbum. Femalesoviposit on the surface of leaves or on leaf buds. The early instar larvae do not make cases and are confínedinside leaves as miners. In the later instars the larvae begin to construct cases made of silk and covered withfeeding debris that are characteristic of Coleophoridae. Only last instar larvae occasionally occur onasparagus shoots, which they do not feed upon but use for pupation sites. In Chile, C. versurella is distributedfrom regions V to IX. C. mayrella is distributed from IX to X regions and its larvae feed on seeds of Trífoliumrepens.